Population fluctuation of Phyllocnistis citrella and its parasi-toids in two citrus species in Western Crete (Greece) - Kalaitzaki, A. P.; Tsagkarakis, A. E.; Lykouressis, D. P. (ENTOMOLOGIA HELLENICA, 2011)
Population fluctuation, percentage of parasitism and parasitoid species composition of Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae) were studied in a citrus orchard with orange and mandarin trees in Chania (Greece), in 1999, three years after the release of the in-troduced parasitoids Citrostichus phyllocnistoides (Narayanan), Quadrastichus sp., Semielacher petiolatus (Girault), Cirrospilus quadristriatus (Subba Rao and Ramamani) and Ageniaspis citricola Logvinovskaya. Results showed that significantly more P. citrella individuals per leaf were recorded on orange than on mandarin trees. Regarding the parasitoid complex composition, the exotic species C. phyllocnistoides, S. petiolatus and Quadrastichus sp., as well as the natives Pnigalio pectinicornis L. and Neochrysocharis formosa (Westwood) were recorded. Among them, C. phyllocnistoides was the most abundant, followed by S. petiolatus. The average percentage of parasitism reached 17% and 22% on orange and mandarin, respectively.